Axial localization and tracking of self-interference nanoparticles by lateral point spread functions - Liu, Yongtao; Zhou, Zhiguang; Wang, Fan; Kewes, Guenter; Wen, Shihui; Burger, Sven; Wakiani, Majid Ebrahimi; Xi, Peng; Yang, Jiong; Yang, Xusan; Benson, Oliver; Jin, Dayong (Nature Communications, 2021)
Sub-diffraction limited localization of fluorescent emitters is a key goal of microscopy imaging. Here, we report that single upconversion nanoparticles, containing multiple emission centres with random orientations, can generate a series of unique, bright and position-sensitive patterns in the spatial domain when placed on top of a mirror. Supported by our numerical simulation, we attribute this effect to the sum of each single emitter’s interference with its own mirror image. As a result, this configuration generates a series of sophisticated far-field point spread functions (PSFs), e.g. in Gaussian, doughnut and archery target shapes, strongly dependent on the phase difference between the emitter and its image. In this way, the axial locations of nanoparticles are transferred into far-field patterns. We demonstrate a real-time distance sensing technology with a localization accuracy of 2.8 nm, according to the atomic force microscope (AFM) characterization values, smaller than 1/350 of the excitation wavelength.
CRIS-Team Scopus Importer:2023-04-20